2021
DOI: 10.1097/gox.0000000000003741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Extended-duration Chemoprophylaxis Regimen for Venous Thromboembolism after Microsurgical Breast Reconstruction

Abstract: Background: Patients undergoing free flap breast reconstruction are at a high risk for venous thromboembolism based upon Caprini scores. Guidelines for venous thromboembolism prophylaxis recommend high-risk groups receive extended chemoprophylaxis for several weeks after gynecological, orthopedic, and surgical oncology cases. Extended prophylaxis has not been studied in free flap breast reconstruction. The purpose of this study was to compare outcomes of free flap breast reconstruction patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Our study demonstrates that the incidence of bleeding complications, hematomas, and operative hematomas are not different between patients who receive outpatient prophylaxis and those who do not, which is consistent with previous studies supporting the safety of inpatient prophylaxis. 10,26,27,35…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study demonstrates that the incidence of bleeding complications, hematomas, and operative hematomas are not different between patients who receive outpatient prophylaxis and those who do not, which is consistent with previous studies supporting the safety of inpatient prophylaxis. 10,26,27,35…”
Section: Discussionmentioning
confidence: 99%
“…Their study results demonstrated a not significant decrease in VTE (1.5% versus 2.8%; P = 0.6) and no significant difference in reoperative hematoma. 27 The ACCP most recently published guidelines for VTE prevention in 2012 and included guidance for plastic surgery patients. The ACCP strongly suggests no specific chemoprophylaxis in very low-risk patients (Caprini score = 0, as defined by the ACCP) and only mechanical prophylaxis (ie, pneumatic compression devices) is necessary in low-risk patients (Caprini score 1 to 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a relative paucity of literature investigating the benefits of this therapy in plastic surgery, 5 and at the time of publication of this work, only one pilot study exists concerning microsurgical breast reconstruction (MBR). 22 …”
Section: Introductionmentioning
confidence: 99%
“…However, there is a relative paucity of literature investigating the benefits of this therapy in plastic surgery, 5 and at the time of publication of this work, only one pilot study exists concerning microsurgical breast reconstruction (MBR). 22 The purpose of this study is to (1) report updated hematoma, DVT, and pulmonary embolism (PE) rates in MBR in the era of strict VTE protocols and increased awareness of the morbidity and mortality of these complications and (2) investigate the benefits and/or potential harms of extended postoperative VTE prophylaxis in patients undergoing MBR, when compared with patients who receive VTE prophylaxis only while hospitalized. This work is intended to guide clinical practice and serve as a foundation for further investigation into this domain.…”
mentioning
confidence: 99%